Rapid-Onset Obesity with Hypoventilation, Hypothalamic Dysfunction, and Autonomic Dysregulation Neuroendocrine Tumor Syndrome: A Rare Cause of Hypothalamic Obesity - A Case Report with Review of Literature - Anurag Mondal; Hriday De; Apurba Ghosh; Priyankar Pal; Debapoma Biswas (Wolters Kluwer Medknow Publications, 2023)
Background: Rapid-onset obesity with hypoventilation, hypothalamic dysfunction, and autonomic dysregulation (ROHHAD) syndrome is a rare cause of obesity, characterized by early and rapid onset of obesity, hypoventilation, hypothalamic dysfunction, and autonomic dysfunction. When there is an associated neuroendocrine tumor, (NET) it becomes ROHHAD NET. Hypothalamic dysfunction causes endocrine problems, respiratory dysfunction, and autonomic alterations. It is difficult to distinguish this clinically from other obesity syndromes of genetic origin unless an individualized strategic approach is used. Clinical Description: We present a case of a 5-year-old developmentally normal girl with excessive weight gain starting in early childhood and the development of a squint. The clinical phenotype of central hypoventilation and autonomic dysfunction, central hypothyroidism, and central precocious puberty satisfied the criteria for ROHHAD syndrome. Management: A right-sided paraspinal supradiaphragmatic mass was identified that was excised and diagnosed as neuroblastoma on histopathology. Since there was no evidence of metastases, chemotherapy was not indicated. Alpha and beta-blockers were started for autonomic dysfunction and high catecholamine levels. Lack of improvement in behavioral manifestations prompted a trial of immunosuppressive therapy, but yielded no results. She ultimately succumbed to a probable cardiorespiratory arrest during sleep. Conclusions: ROHHAD syndrome should be considered a differential diagnosis in rapid-onset monogenic obesity and should be managed with a multidisciplinary approach. Prognosis is guarded due to sudden life-threatening events secondary to autonomic dysfunction.